2008
DOI: 10.1017/s1368980008002577
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment of charitable meal programmes serving homeless people in Toronto

Abstract: Objectives: To assess the potential nutritional contribution of meals provided in a sample of community programmes for homeless individuals, to determine the effect of food donations on meal quality and to develop food-based guidance for meals that would meet adults' total nutrient needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 39 publications
7
43
1
Order By: Relevance
“…This finding of soup kitchens serving low-nutrient-dense meals is consistent with other studies. 7,8,32,33 Of note is that though Kitchen A meals were the only meals that provided adequate energy, vitamin C, and zinc, the meals contained high amounts of fat and sodium. Moreover, even with the higher energy content, Kitchen A meals provided significantly less magnesium, calcium, and dietary fiber than the goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding of soup kitchens serving low-nutrient-dense meals is consistent with other studies. 7,8,32,33 Of note is that though Kitchen A meals were the only meals that provided adequate energy, vitamin C, and zinc, the meals contained high amounts of fat and sodium. Moreover, even with the higher energy content, Kitchen A meals provided significantly less magnesium, calcium, and dietary fiber than the goals.…”
Section: Discussionmentioning
confidence: 99%
“…Similar prior studies relied on menus, recipes, or cooks' recollections to analyze food served, whereas this study identified specific ingredients and amounts used in the food served and accounted for the preparation method in the nutrient analysis. 8,33,38 This method was chosen for increased accuracy, because the soup kitchen directors acknowledged that menus and recipes were often not available, or followed, due to lack of planning and irregular food donations.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of intake of vitamins and minerals has also been noted as an issue in other countries [12][13][14]. In order to improve the nutritional status of the homeless population, sufficient amounts of vegetables and fruits must be provided.…”
Section: Problem On Nutrition and Food Qualitymentioning
confidence: 99%
“…3 Soup kitchens, or community meal centers, regularly serve food-insecure and homeless individuals. [4][5][6][7][8][9][10] These meal centers play an important role in filling the food gap. However, studies have indicated that meals provided at these sites are often nutritionally inadequate, and low in nutrient-dense fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have indicated that meals provided at these sites are often nutritionally inadequate, and low in nutrient-dense fruits and vegetables. 4,[6][7][8][9][10] The co-morbidity of food insecurity and obesity [11][12][13][14][15][16] calls for a closer examination of the amounts and types of food served and consumed at these sites. If the meal centers do not, in fact, provide appropriate serving sizes of nutrient-dense foods (such as lean protein, fruits, and vegetables), or if the food served is not consumed because it is unpalatable, cannot be chewed, or is culturally inappropriate, meal-center guests may fail to receive adequate nutrition.…”
Section: Introductionmentioning
confidence: 99%